Characteristics of intracellular Ca2+ signals consisting of two successive peaks in hepatocytes during liver regeneration after 70% partial hepatectomy in rats - Taira Z; Ueda Y; Monmasu H; Yamase D; Miyake S; Shiraishi M (Dove Medical Press, 2016)
Zenei Taira, Yukari Ueda, Hiroshi Monmasu, Daisuke Yamase, Sayaka Miyake, Maya Shiraishi Faculty of Pharmaceutical Sciences, Tokushima Bunri University, Tokushima, Japan Abstract: Two specific signals for regulating liver regeneration were found after 70% partial hepatectomy (PH) in rats. The first finding was a sustained increasing signal of intracellular Ca2+ ([Ca2+]i) in hepatocytes, consisting of two successive peaks with the first narrow peak at 1 hour and the second broad peak increasing by day 3 and then returning to normal by day 4. The second finding was an abnormal peak in the restoring ratio (Rr) curve of liver regeneration after 70% PH at day 4, where the Rr exceeded 100% temporarily, returned to a lower level, and then proceeded to a termination phase of liver regeneration. For 4 days around the two successive [Ca2+]i peaks and abnormal peak, various physiological activities were induced to promote liver regeneration after 70% PH. mRNA expression of genes encoding Ca2+-binding proteins S100A4 and calpain was induced between the two Ca2+ peaks. Hepatocytes underwent synchronous cell proliferation as the liver was restored from 30% to 70% at day 4, and significant expression of VEGF mRNA at around day 4 promoted angiogenesis to remodel the sinusoidal system. Cytochrome P450 activity levels in microsomes and alanine aminotransferase values at 24 hours after CCl4 administration were decreased after 70% PH, which recovered transiently to the control level at day 4, returned to the decreased level, and then slowly recovered by day 10. Thus, these results indicate that day 4 is important during liver regeneration after 70% PH. Keywords: partial hepatectomy, ratio of liver regeneration, intracellular Ca2+, S100A4, termination signal